Design and Development of an Accounting Information System Using Microsoft Access at Toko Glory - Ivone; Angelica (ConCEPt - Conference on Community Engagement Project, 2025)
In the business world, the application of technology plays a crucial role in ensuring that business operations run smoothly and efficiently. This community service activity focused on the design and development of a Microsoft Access-based financial recording system aimed at improving the performance and effectiveness of partner business operations, as well as supporting decision-making and strategic planning processes. The method used was a descriptive-analytical approach, which included the stages of identifying user needs, system design, testing, and evaluating the results of the implementation of the developed system. The results of the activity indicated that the system was able to assist business owners in recording financial transactions in a computerized manner, generating financial reports automatically, and minimizing errors in the recording process. The implementation of this system is expected to facilitate business owners in accurately monitoring financial conditions, increasing efficiency, and strengthening overall business management. In the future, the system can be developed by integrating the database into an online server, such as SQL Server or SharePoint, to centralize data access and improve the security and efficiency of financial information management.